Evaluation of Serum Level and Interleukin-4 Receptor (rs1805010) Gene Polymorphism in a Sample of Osteoporosis Women - Hammadi, Zainab Abdulrahman; Salih, Maan Hasan; Rija, Firas Faris (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: Osteoporosis is characterized by subtle skeletal degeneration and bone loss, generally defined as a systemic metabolic disease. Interleukin-4 receptor (IL-4) R has been associated with osteoimmune, the relationship between the immune system and the skeleton (osteoimmune system) is studied in osteoimmunology. Objectives: In this study, we aimed to investigate the serum level and polymorphisms to genotype IL-4R )rs1805010 ( and their effect on osteoporosis in Iraqi women. Methods: ELISA was used to determine the serum level of the IL-4R and polymerase chain reaction (PCR) to genotype the IL4R gene in 90 Iraqi women (60 patients with osteoporosis and 30 control groups). Results: The main findings on the IL-4R polymorphism (rs1805010) indicated that there was no association for the prediction of osteoporosis in Iraqi women. Whereas, there was a significant increase in serum levels of interleukin-4 receptor in women with osteoporosis compared to healthy women, (P = 0.018). Conclusion: The study supposes that there is a link between the serum level of IL4R and how osteoporosis develops, but IL4R gene polymorphisms may not play a role in osteoporosis in women. Keywords: Osteoporosis, rs1805010, IL4R, Polymorphism.